2016
DOI: 10.21037/cdt.2016.05.02
|View full text |Cite
|
Sign up to set email alerts
|

Daily cardiac catheterization procedural volume and complications at an academic medical center

Abstract: Background: Over 1,000,000 cardiac catheterizations (CC) are performed annually in the United States.There is a small risk of complication that has persisted despite advances in technology. It is unknown whether daily CC procedural volume can influence this risk. In an effort to improve outcomes at our academic medical center, we investigated the relationship between daily CC volume and complication rates.Methods: We obtained data from both the National Cardiovascular Data Registry (NCDR) Cath-PCI and Lumedx© … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Moreover, it has been suggested that rapid ventricular pacing may increase the risk of sustained ventricular arrhythmias compared to the baseline risk of cardiac catheterisation (less than 1%). 29 In our institutional series, three neonates (8%) developed ventricular fibrillation at the onset of rapid right ventricular pacing and were successfully defibrillated. Their procedures were completed with rapid right ventricular pacing at lower pacing rates by 20 bpm.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, it has been suggested that rapid ventricular pacing may increase the risk of sustained ventricular arrhythmias compared to the baseline risk of cardiac catheterisation (less than 1%). 29 In our institutional series, three neonates (8%) developed ventricular fibrillation at the onset of rapid right ventricular pacing and were successfully defibrillated. Their procedures were completed with rapid right ventricular pacing at lower pacing rates by 20 bpm.…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, RRVP does have certain pitfalls, including a prolongation in operative time and a potentially higher risk of cardiac perforation and pneumothorax (if performed via the jugular/subclavian vein)[ 18 ]. It has also been suggested that rapid ventricular pacing may increase the risk of sustained ventricular arrhythmias compared to the baseline risk of cardiac catheterization (< 1%)[ 31 ]. According to our findings, only one (1.4%) case of ventricular fibrillation has been described, which was still successfully defibrillated[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This decline has been accompanied by an increase in PCI revascularization. Over 1,000,000 cardiac catheterizations are performed annually in US (45). Hence, significant improvements in the technology of coronary stents and vascular grafts is necessary to meet the clinical demand.…”
Section: New Options In Cardiac Revascularizationmentioning
confidence: 99%